Influence of DNA-binding compounds with cancer preventive activity on the mechanisms of gene expression regulation - K. I. Kirsanov; O. A. Vlasova; T. I. Fetisov; R. G. Zenkov; E. A. Lesovaya; G. A. Belitsky; K. Gurova; M. G. Yakubovskaya (Успехи молекулярной онкологии)
The presented review is devoted to the analysis of molecular mechanisms of action for different natural DNA-tropic compounds with established tumor preventive activity. Here we present their cancer preventive effects observed in vivo, mechanisms of DNA binding, influence on epigenetic regulation and “housekeeping” protein function. Additionally, the influence of these compounds on DNA helix parameters is discussed that should impact on epigenetic regulation of gene expression and formation of topologically associated domains.